Effects of hexagonal boron nitride on dry compression mixture of Avicel DG and Starch 1500 - UĞURLU, TİMUÇİN (TAYLOR & FRANCIS LTD, 2016)
The objective of this study was to investigate the lubrication properties of hexagonal boron nitride (HBN) on a (1:1) binary mixture of Avicel DG and Starch 1500 after using the dry granulation-slugging method and compare it with conventional lubricants, such as magnesium stearate (MGST), glyceryl behenate (COMP) and stearic acid (STAC). MGST is one of the most commonly used lubricants in the pharmaceutical industry. However, it has several adverse effects on tablet properties. In our current study, we employed various methods to eradicate the work hardening phenomenon in dry granulation, and used HBN as a new lubricant to overcome the adverse effects of other lubricants on tablet properties. HBN was found to be as effective as MGST and did not show any significant adverse effects on the crushing strength or work hardening. From the scanning electron microscope (SEM) images, it was concluded that HBN distributed better than MGST. As well as showing better distribution, HBN's effect on disintegration was the least pronounced. Semi-quantitative weight percent distribution of B and N elements in the tablets was obtained using EDS (energy dispersive spectroscopy). Based on atomic force microscope (AFM) surface roughness images, formulations prepared with 1% HBN showed better plastic character than those prepared with MGST.
Keywords: Cohesion index; dry granulation; hexagonal boron nitride; lubricant effectiveness; lubricants; slugging; EXTERNAL LUBRICATION; MAGNESIUM STEARATE; POWDER; COMPACTION; TABLETS; NANOTRIBOLOGY; RECOMPRESSION; EXCIPIENTS; NANOTUBES; GRANULES